Solo instrumental and chamber music; its story told through the lives and works of its foremost composers. - Ewen, David, 1907-1985. (New York, F. Watts, 1974)
Traces the history of solo instrumental and chamber music discussing important composers and their works.
Keywords: Instrumental music -- History and criticism; Chamber music -- History and criticism; Composers